A DC offset removal algorithm based on AR model - Kim, Woo-Joong; Kang, Sang-Hee (Journal of International Council of Electrical Engineering, 2018)
This work proposes an auto-regressive (AR) model-based algorithm that can eliminate the adverse influence of the exponentially decaying DC offset in the phasor estimation process using discrete Fourier transform (DFT). The proposed algorithm comprises three stages: DFT, AR model implementation, and compensation. First, DFT can eliminate all harmonic components and estimate the phasor of the fundamental frequency component. Second, the AR model is used to calculate the error caused by the exponentially decaying DC offset in the phasor value estimated by DFT. A second-order AR model that uses three successively estimated phasor values is utilized. Finally, the phasor of the fundamental frequency component can be accurately estimated by compensating the error caused by the exponentially decaying DC offset. The performance of the proposed algorithm is evaluated for a-phase to ground fault on a 154 kV 25 km overhead transmission line. Electromagnetic Transients Program is used to generate fault signals. The evaluation result suggests that the proposed algorithm can effectively suppress the adverse influence of the DC offset.